1992
DOI: 10.1007/bf00120994
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for De Novo rearrangements of Drosophila transposable elements induced by the passage to the cell culture

Abstract: The genomic distribution and the number of elements of eleven transposon families have been compared by the Southern technique between permanent cultured cells, larval salivary glands and the brains and whole flies of an inbred Drosophila line (inb-c) from which the cells were established. In cultured cells, changes in restriction patterns consistent with various types of rearrangements such as amplification, transposition and excision of the elements of copia, 1731, 412, 297 and mdg-4 transposon families are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
(49 reference statements)
4
16
0
Order By: Relevance
“…In the FHVvirion-RNAseq dataset, the mutation frequency was 8.7 × 10 −4 for FHV RNA 1 and 9.8 × 10 −4 for FHV RNA 2. These values are within the range of the estimated Transposon ′1731′ is known to be highly duplicated in cell lines (28). ‡ See Dataset S4 for further details.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In the FHVvirion-RNAseq dataset, the mutation frequency was 8.7 × 10 −4 for FHV RNA 1 and 9.8 × 10 −4 for FHV RNA 2. These values are within the range of the estimated Transposon ′1731′ is known to be highly duplicated in cell lines (28). ‡ See Dataset S4 for further details.…”
Section: Resultssupporting
confidence: 63%
“…Strikingly, 89,559 reads mapped to transposable elements, which corresponds to 0.1% of the total encapsidated RNA. Most of these are Class I LTR retrotransposons (Table 2), which are the most abundant transposons in the D. melanogaster genome (27,28). Interestingly, unlike the mRNAs, a number of the transposable elements are present in both positive and negative sense directions (e.g., Gypsy, Springer, and Diver).…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, short-term cultured cells promote transposition of the copia-like elements 412, 1731 and 297 (Junakovic et al, 1988) and 1731 element (Maisonhaute et al, 2007). However, mobilization is not observed in long-term cultured cells (Junakovic et al, 1988) or in other experiments where the TE mobilization was only observed for most copia-like elements, whereas B104 (gypsy-like), G (non-long terminal repeat retrotransposon) and blood (copia-like) elements remain stable (Di Franco et al, 1992). In the case of 1731 mentioned above, all new copies seem to be derived from a unique master copy slightly active in Drosophila genome and strongly activated during the establishment of the cell culture.…”
Section: Biotic Stressesmentioning
confidence: 96%
“…Although there are no relevant data from asexual species, transposition of DNA and RNA elements is known to occur pre-and postmeiotically and in somatic cells and is reflected in the significant increase in TE copy number during the establishment and propagation of tissue culture lines. (57)(58)(59)(60)(61)(62)(63)(64) Limitations on DTE copy number So long as DTEs within a genome engage in replicative transposition, their number can be stabilized only by mechanisms the effectiveness of which is an increasing function of their number. (65,66) That such mechanisms exist in sexually reproducing systems is self-evident, as otherwise, given the excess of transposition over decay and excision, DTEs would increase indefinitely.…”
Section: à4mentioning
confidence: 99%